Performance of n-TiO2/dye/p-Cul Incorporated with New Chelating Agent for Solid State DYE Sensitized Solar Cell Applications - Ayib Rosdi, Zainun; M., Ichimura (2013)
A new approach to produce CuI-related composite film for dye-sensitized solar cells applications is demonstrated.